Hygrothermal Effect on the Impact Response of Carbon Composites with Epoxy Resin Enhanced by Nanoclays - Reis, Paulo Nobre Balbis dos (2022)
This paper presents the results of the hygrothermal effect on the impact response of carbon/epoxy composites and the benefits gained from doping the epoxy resin with nanoclays previously subjected to a silane treatment appropriate for the resin. The nanoclay reinforcement increased the maximum load and the elastic recovery of the composites. The thermal degradation caused by exposure to 60°C for 10 days was insignificant, while the immersion in water at 60ºC for 30 days led to a continuous reduction in the maximum load and the elastic recovery. Multiple impacts resulted in a continuous and nearly linear degradation of the impact response both of dry and environmentally assisted specimens.